Perfectly pegasus - Sima, Jessie (New York : Simon & Schuster Books for Young Readers, 2022)
Nimbus, a lonely pegasus, searches for a fallen star to wish for a friend and meets a unicorn named Kelp along the way.
K-3
AD550L
Some copies purchased with funds from an OASL Connie Hull Mini-Grant, Mt. View 2024
Keywords: Friendship -- Juvenile fiction; Pegasus (Greek mythology) -- Juvenile fiction; Unicorns -- Juvenile fiction; Wishes -- Juvenile fiction; Animals, Mythical -- Juvenile fiction; Friendship -- Fiction; Pegasus (Greek mythology) -- Fiction; Unicorns -- Fiction; Wishes -- Fiction; Animals, Mythical -- Fiction; Fantasy fiction